Seismic Data, Photographic Images and Physical Modeling of Volcanic Plumes as a Tool for Monitoring the Activity of Nevado del Ruiz Volcano, Colombia - Londono, John Makario; Galvis, Beatriz (Frontiers in Earth Science, 2018)
Quantification of volcanic plume parameters is a fundamental task to know the behavior of an active volcano. Volcanic plume mass, flow rate and ash injection were determined from integration of scaling laws of several volcanic plume models, seismic data, and photographic images for the period 1985–2017 for Nevado del Ruiz Volcano (NRV), Colombia, with the aim to quantify the ash emitted volume during this period and to establish a relationship between seismicity and those volcanic plume parameters. The results show a decrease of ~ two orders of magnitude in the volume of ash plumes from the November 13, 1985 eruption (0.12 km3) to the September 1, 1989 eruption (1.43x10-3 km3). This pattern is preserved for the June 30, 2012 eruption and 2015-2017 eruptive cycle, with volumes five times smaller than in 1989. The results also show a correlation between radiated seismic energy (RSE) of the volcanic tremor and ash load for higher (>1 km) and longer-duration (>240 s) plumes. It was possible to calculate a minimum value of ash load based on radiated seismic energy (RSE) release and reduced displacement (RD) of volcanic tremor signal associated with the eruption, which could be used as a monitoring tool. Moreover, for the period 2015-2017 changes in volume of ash plume were correlated with changes in reduced displacement (RD, a way of normalizing volcanic tremor to a common scale) and RSE, associated with different stages of volcanic activity. The continuous decreasing of ash plume volumes from 1985 to 2017 suggests a same volcanic cycle almost ending. On the other hand, the evidence of new magmatic input in 2007 might suggest that a new volcanic cycle started on that date and still in process of magma ascending. Probably in the next future surface evidence of the new cycle can be observed at NRV or other volcanoes around it.